Akibat Hukum Perjanjian Restrukturisasi Kredit Mobil Pada Masa Covid 19 (Studi Pada PT. Adira Dinamika Multi Finance Tbk., Cabang Bengkulu 2 Car) - Muhammad Rizky (Iuris Studia: Jurnal Kajian Hukum, 2021)
The COVID-19 pandemic that occurred in Indonesia not only caused infectious diseases that caused many deaths, but also resulted in congestion in the wheels of the people's and country's economy. This research is normative and descriptive analysis. The data collection technique is library research (library research). Data analysis is qualitative. The results of the discussion in this study are the government's appeal and this has been regulated in OJK Regulation No. 14/POJK.05/2020 concerning Countercyclical Policy on the Impact of the 2019 Coronavirus Disease Spread for Non-Bank Financial Services Institutions. The form of restructuring policy carried out by PT Adira Dinamika Multi Finance Tbk Bengkulu 2 Car Branch to debtors is listed in Temporary Decree No.KS-020C/RISKLGL/COLL/V/2021 issued by Adira Finance. PT Adira Dinamika Multifinance Tbk Bengkulu 2 Car Branch carried out a consumer financing restructuring program due to the pandemic factor which resulted in the community's economy declining and experiencing significant changes in income